The robber barons; the great American capitalists, 1861-1901. - Josephson, Matthew, 1899-1978. (New York, Harcourt, Brace & World, 1962)
Includes material on John D. Rockefeller, J. Pierpoint Morgan, Cornelius Vanderbilt, William H. Vanderbilt, Andrew Carnegie, E. H. Harriman, Jay Gould, Jim Fisk, Jay Cooke, Daniel Drew, Henry C. Frick, James J. Hill, Charles M. Schwab, Henry Villard, Standard Oil Company, trusts
The national scene: the national character -- What the young men dream -- Of empire-builders -- The winning of the West -- Two captains of industry -- The fight for Erie -- Grandeurs and miseries of empire-building -- Rising from the ruins -- Mephistopheles -- Caesar Borgia in California -- Giants of the Northwest -- Certain industrialists arose -- Morgan and the railways -- The robber barons -- Again the robber barons -- Concentration: the great trusts -- The empire of Morgan -- Battle of giants.
Includes bibliography.
Keywords: Capitalists and financiers -- United States; Industries -- United States -- History; Railroads -- United States -- History; Capitalists and financiers -- United States; Industries -- United States -- History; Railroads -- United States -- History